Intimate Enemies and Intimate Allies: Land Conflicts and Microreconciliation After War in Northern Uganda - Obika, Julaina (Advances in Social Sciences Research Journal, 2022)
Land conflicts after war in northern Uganda have been given scholarly attention, often taking different directions. This article focuses on microreconciliation at the local level to unpack how people who returned to their ancestral lands are faced with the challenges of re-establishing intimacy after years of encampment during the war. Juxtaposing the notions of intimate enemies and intimate allies, I illustrate how intimacy and reconciliation may be difficult to achieve between families, clans and neighbours. Witchcraft accusations is not a new phenomenon but I show how accusations are used in new ways as strategies to outlaw and excommunicate others from customary land. Dividing land, another strategy to create closeness or distance between kith and kin is often seen as a solution to land conflicts even though it goes against the clan rules that used to govern Acholi society before the war.